Retropharyngeal calcific tendinitis: A rare, benign, but painful condition with stiff neck. (17th July 2020) - Akaishi, Tetsuya; Miura, Keiki; Iduma, Masaaki; Ishii, Tadashi
Abstract : A 51‐year‐old afebrile man visited the hospital with acute severe neck pain with stiff neck, but cervical CT showed no calcification around the odontoid process. Cervical MRI revealed prevertebral hyperintense area of edema at the C1‐C5 vertebral bodies, providing the diagnosis of retropharyngeal calcific tendinitis. The patient was spared for lumbar puncture, and his symptoms swiftly disappeared only with oral NSAIDs.